La infraestructura educativa y el aprendizaje de los niños de primer año de educación básica del jardín de Infantes “Antonio Jaramillo” del cantón Guano, provincia de Chimborazo, período 2015 - Sinchi Damian, Myriam Janneth (2016)
The present study was conducted in the Kindergarten called "Antonio Jaramillo" located in Guano, province of Chimborazo. It was important to know the educational infrastructure in some areas since its installations are not adequate, they were in poor condition and bathrooms of children are in poor conditions, without water service that constitutes a fundamental part in the teaching and learning process, one of the characteristics of the physical infrastructure of the institution contributes to shape the environments where children learn to give them a rich source of knowledge when learning, since at the present time, educational institutions must have adequate infrastructure for a good quality of education, where children should feel happy to go to learn new skills. This study is divided into chapters which explains in detail how the thesis is structured and leading to its realization and importance to keep improving every day training centers and learning of children. For the preparation of this research work: Educational Infrastructure and dependent: the operationalization of the variables, Independent was conducted. Learning methods was used: scientific, inductive and deductive analysis and synthesis of the same for the realization of the performed investigation. The techniques used were: a survey applied to teachers and a direct observation to children, instruments like a questionnaire and an observation sheet. To conclude, findings, and recommendations are presented along with the bibliographic evidence.